Deep-learning enabled generalized inverse design of multi-port radio-frequency and sub-terahertz passives and integrated circuits - Karahan, Emir Ali; Liu, Zheng; Gupta, Aggraj; Shao, Zijian; Zhou, Jonathan; Khankhoje, Uday; Sengupta, Kaushik (Nature communications, 2024)
Millimeter-wave and terahertz integrated circuits and chips are expected to serve as the backbone for future wireless networks and high resolution sensing. However, design of these integrated circuits and chips can be quite complex, requiring years of human expertise, careful tailoring of hand crafted circuit topologies and co-design with parameterized and pre-selected templates of electromagnetic structures. These structures (radiative and non-radiative, single-port and multi-ports) are subsequently optimized through ad-hoc methods and parameter sweeps. Such bottom-up approaches with pre-selected regular topologies also fundamentally limit the design space. Here, we demonstrate a universal inverse design approach for arbitrary-shaped complex multi-port electromagnetic structures with designer radiative and scattering properties, co-designed with active circuits. To allow such universalization, we employ deep learning based models, and demonstrate synthesis with several examples of complex mm-Wave passive structures and end-to-end integrated mm-Wave broadband circuits. The presented inverse design methodology, that produces the designs in minutes, can be transformative in opening up a new, previously inaccessible design space. Authors report an AI enabled design method for the synthesis of radio-frequency and millimetre-wave integrated circuits. It can discover architectures beyond human intuition and synthesizes these circuits with given specifications within minutes.